Off-stage! : Sketches from the English Teaching Theatre - Doug Case; Ken Wilson (London Heinemann Educational Books, 1979)
An ELT activity book based on a selection of 15 sketches from the English Teaching Theatre Group. An accompanying teacher's book and a cassette are also available
Keywords: English language -- Study and teaching -- Foreign speakers; Role playing; English language -- Comprehension -- Questions & answers -- For non-English speaking students